Pengaruh Harga, Iklan, dan Kualitas Produk terhadap Keputusan Pembelian Layanan Internet Telkomsel - Saputra, Murjani; Putra, Dwi Ardi Wicaksana (Keizai, 2021)
This study aims to determine the effect of price, advertising, and product quality on purchasing decisions. The sampling technique used is convenience sampling with a total of 70 respondents. This research instrument uses a questionnaire using a Likert scale to collect data on price, advertising, and product quality onpurchasing decisions. The results of this study indicate that the price partially does not have a significant effect on purchasing decisions. Then advertising partially has a significant positive influence on purchasing decisions. Product Quality partially does not have a significant effect on purchasing decisions. Simultaneously stated that the influence of price, advertising, and product quality together affect the decision to purchase Telkomsel internet services. The results contribute that the role of internet service advertising is indispensable in marketing internet products in rural areas.